Development of Bilingual Teaching Materials for Logical Reasoning Through Visual Studio Code - Mutiara Ani Sabina; Netriwati Netriwati; Riyama Ambarwati; Fadly Nendra (Education and Talent Development Center Indonesia (ETDC Indonesia), 2026)
The demands of 21st-century learning emphasize strengthening logical reasoning and digital literacy, while schools and Islamic boarding schools still lack technology-based bilingual teaching materials that are proven to be valid, practical, and effective..This study aims to develop and test the feasibility, practicality, and effectiveness of bilingual teaching materials (Indonesian and Arabic) on the subject of Two-Variable Linear Equation Systems (SPLDV) through Visual Studio Code (VS Code) to improve students' mathematical logical reasoning. This research is motivated by the low ability of students' mathematical logical reasoning and the limitations of innovative learning resources that integrate bilingual aspects and digital technology. The method used is Research and Development (R&D) with the ADDIE model, implemented on grade VIII students at Darul Falah Islamic Boarding School and Nashihuddin Islamic Junior High School in Bandar Lampung. The results of the study show that the teaching materials developed are declared Very Valid/Very Appropriate based on expert assessments (material experts 96.88%, media experts 87.5%, and language experts 100%) and are considered Interesting (practical) by students with an average positive response above 80%. Furthermore, the effectiveness test proved that the use of bilingual teaching materials based on Visual Studio Code was significant in improving mathematical logical reasoning, as evidenced by the average N-gain value which was in the medium category (Small Trial 0.563 and Large Trial 0.596). Thus, it can be concluded that bilingual teaching materials through Visual Studio Code are feasible, practical, and effective to be used as a learning innovation to improve students' mathematical logical reasoning abilities.